One piece. East blue. Volumes 10, 11, 12 - Oda, Eiichiro, 1975-; Caselman, Lance (Shonen Jump., 2010)
Hoping to solve a problem back in her hometown, Nami turns her back on her family and friends to serve the leader of the Fish-Man pirates, "Saw-Tooth" Arlong. When Arlong goes back on his word, however, Nami has no choice but to turn to those she has been lying to for help.